Analysis of biomass availability for energy use in Sicily. (December 2015) - Chinnici, Gaetano; D'Amico, Mario; Rizzo, Marcella; Pecorino, Biagio
Abstract: This paper analyses and estimates the availability of biomass in Sicily, an area characterized by Mediterranean crops, to be subsequently exploited in anaerobic fermentation processes in order to produce thermal or bio-methane electricity. This analysis contains the assessment of biomass quantities potentially available in five categories: waste and by-products from processing, livestock sewage, agricultural residues, waste from agricultural processing residues of marketing and dedicated bioenergy crops. The estimates of raw materials are based on statistics from 2013, by applying a series of parameters obtained from a wide review of current literature and direct research. The quantities of biomass estimated add up to 3, 910, 649.1 t/year; such quantities demonstrate that Sicily has great potential, finally allowing it to bridge the gap in energy production coming from biomass in comparison to the other regions in the north of Italy. The appraisal of available biomass lays down the conditions for starting studies to estimate the energy obtainable and the assessment of the technical-economic feasibility of the use of remaining biomass available as a source of alternative energy.